2021
DOI: 10.31635/ccschem.021.202100771
|View full text |Cite
|
Sign up to set email alerts
|

Assembly Induced Super-Large Red-Shifted Absorption: The Burgeoning Field of Organic Near-Infrared Materials

Abstract: Supramolecular assembly of organic dye compounds with J-aggregation leads to a red-shifted absorption spectrum that greatly facilitates the construction of near-infrared (NIR) materials. A considerable improvement of the material functions requires that the absorption red-shift be larger than 100 nm, but such a super-large red-shift is challenging, and the rules leading to the super-large red-shifted absorption is still not explicit. In this review, we focused on those J-aggregated organic dye materials with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 54 publications
3
40
0
1
Order By: Relevance
“…[ 13 ] For spherical morphology of PFF‐NPs, it is the balance between hydrophobic interaction and electrostatic force that plays a key role in forming the well‐dispersed colloidal nanoparticles. [ 6c ] Dynamic light scattering (DLS) results revealed that the PFF‐NPs had a diameter of 80 ± 25 nm (Figure 1b), consistent with the microscopic observation. The zeta potential values of the PD‐NFs, PDD‐NFs, PDDDD‐NFs, PFF‐NPs, and PYY‐NFs were determined to equal −25.3 ± 6.0 mV, −25.0 ± 6.1 mV, −28.5 ± 6.7 mV, −30.9 ± 8.0 mV, and −28.8 ± 6.7 mV, respectively (Figure 1c).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…[ 13 ] For spherical morphology of PFF‐NPs, it is the balance between hydrophobic interaction and electrostatic force that plays a key role in forming the well‐dispersed colloidal nanoparticles. [ 6c ] Dynamic light scattering (DLS) results revealed that the PFF‐NPs had a diameter of 80 ± 25 nm (Figure 1b), consistent with the microscopic observation. The zeta potential values of the PD‐NFs, PDD‐NFs, PDDDD‐NFs, PFF‐NPs, and PYY‐NFs were determined to equal −25.3 ± 6.0 mV, −25.0 ± 6.1 mV, −28.5 ± 6.7 mV, −30.9 ± 8.0 mV, and −28.8 ± 6.7 mV, respectively (Figure 1c).…”
Section: Resultssupporting
confidence: 79%
“…[ 5 ] Therefore, supramolecular photothermal nanodrugs constructed through the self‐assembly of biomolecules have been proposed as promising candidates for cancer PTT. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the packing mode of F 4 TCNQ‐based CT complexes plays a crucial effect to dominate their optoelectronic properties. [ 8 ] Electron spin resonance (ESR) measurements were performed to study the relationship between the packing mode, radical concentration, and optoelectronic features in the CT complex. As shown in Figure 1c, these prepared F 4 TCNQ‐based CT complexes present the obvious ESR signal, which is consistent with the character of the CT interaction in ground state.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] The functionalities of molecular superstructures are strongly dependent on the intermolecular packing because of the strong coupling between the electronic and structural dynamics of the molecular units in the solid state. In particular, the electron transport, 5 fluorescence, 6 and electronic absorption 14,15 of solid assemblies from conjugated molecules are strongly associated with aggregated structures. For example, the parallel aligned aromatic chromophores in various supramolecular assemblies with tilt angle (θ) <54.78°(J-aggregate definition) allow electronic excitation from the ground state to the excited state with lower energy relative to the monomeric molecules, resulting in an absorbance bathochromic-shift (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%